The Influence of Participatory Leadership and Teacher Competence on Performance with Organizational Commitment - Junaris, Imam (Al-Hayat: Journal of Islamic Education, 2023)
This study examines the mediating role of organizational commitment on the effect of participatory leadership and competency on teacher performance. This research consists of two independent variables, participatory leadership and competence, one mediating variable, organizational commitment, and one dependent variable, teacher performance. The research method used is quantitative. Explanative research approach with a survey approach. The test was carried out at the Tulungagung State Aliyah Madrasah with a total sample of 100. Data analysis in this study used Partial Least Square (PLS) analysis using Smart PLS. The results of the survey show that participatory leadership has a significant effect on teacher performance. Thus the higher the participatory leadership, the higher the teacher's performance. Teacher competence has a significant impact on teacher performance. Thus, the higher the teacher's competence, the higher the teacher's performance; this proves that teacher competence substantially affects organizational commitment. Likewise, the higher the teacher's competence, the higher the organizational commitment, as evidenced by the significant effect organizational commitment has on teacher performance. Meanwhile, as a mediating variable, the higher the organizational commitment, the higher the teacher's performance. These results can be a reference for anyone involved in the world of work, especially teachers, to strengthen commitment so that version can run well continuously.